The castle chronotope in J. Kerouac’s novel «Doctor Sax» - Дюрба, Діна Вікторівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The category of artistic space is an indispensable text part of the piece of art. One of the metaphors for road is its goal, namely the search for material or spiritual values. However, sometimes the value of the road lies within itself. The road, the way are the important philosophical and aesthetic parts of American literature. The road usually has at least two points in space such as the beginning and the end. As a rule, various obstacles are between them, and the heroes overcome them to achieve their goal. Compared with it, representatives of the beat generation literature transform their views on the road.The space category is an important part of the plot, stylistic, and compositional lines of the piece of art. Travelling as a metaphor for life journey people pass through is one of the topmost poetics elements in J. Kerouac’s novel.The image of the castle in the novel combines the features of a truly existing architectural structure with fantastic features. First of all, this is a description of the place where the castle is located. The irreality of the castle is emphasized by the numerous descriptions of the superhuman creatures that inhabit it – vampires, werewolves and others. The castle chronotope study in Doctor Sax allowed highlighting such features of the poetics of J. Kerouac’s myth-and-symbolic world modeling as use of castle chronotope as such meaning the narrator’s unreal dreams and place he sees them promoted by inhuman beings, use of serpent character as embodiment of world evil and death symbolics (visions of the mine-graves, the River of Death, People’s Death, dark colors variety, rain motive).